2007
DOI: 10.1159/000101899
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Liver Cancer

Abstract: Surgical treatment of hepatocellular carcinoma (HCC) has developed remarkable for several reasons. The surgical mortality rates of patients with HCC after hepatectomy have decreased due to appropriate criteria for surgery, refined surgical techniques and improvement in the pre- and postoperative management. In preoperative management, refinements in liver function tests and strategies for esophageal varices, and the induction of preoperative portal vein embolization have contributed favorably to the outcome af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In the clinical practice, hepatectomy is the most effective method for the radical cure of primary malignant hepatobiliary tumors. 28,29 Before hepatectomy, evaluating liver functional reserve is needed to avoid postoperative liver failure. Previous studies have shown that the liver elasticity values measured using Virtual Touch Quantification were moderately to strongly correlated with liver functional reserve, using the indocyanine green excretion test and technetium-99m-diethylenetria-minepentaacetic acid-galactosyl-human serum albumin scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical practice, hepatectomy is the most effective method for the radical cure of primary malignant hepatobiliary tumors. 28,29 Before hepatectomy, evaluating liver functional reserve is needed to avoid postoperative liver failure. Previous studies have shown that the liver elasticity values measured using Virtual Touch Quantification were moderately to strongly correlated with liver functional reserve, using the indocyanine green excretion test and technetium-99m-diethylenetria-minepentaacetic acid-galactosyl-human serum albumin scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical practice, hepatectomy is the most effective method for the radical cure of primary malignant hepatobiliary tumors 28,29 . Before hepatectomy, evaluating liver functional reserve is needed to avoid postoperative liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct cancer (BDC) and hepatocellular carcinoma (HCC) are the most common malignant tumors of the hepatobiliary system. Hepatectomy is the most effective method for the radical cure of hilar BDC (HBDC), intrahepatic BDC (IHBDC), and HCC (Nimura et al 1998;Miyazaki et al 2007), however, excessive hepatectomy has a high risk of liver failure in BDC and HCC patients (Breitenstein et al 2010;Lock et al 2009). To reduce post-hepatectomy morbidity and mortality, preoperative assessment of liver functional reserve is important (Mizumoto et al 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Even after liver resection, overall prognosis is poor [ 22 – 24 ]. 1-year survival rates after surgical resection are 80-90 %, falling to 41-74 % at 5 years [ 12 , 25 , 26 ]. Unfortunately less than 20 % of patients are surgical candidates because of advanced disease stage at presentation.…”
Section: Introductionmentioning
confidence: 99%